Magnesium alloy corrosion-resistant coating and use method thereof
By applying a corrosion-resistant coating containing epoxy resin, phenolic resin and modified inorganic filler on the surface of the magnesium alloy, and combining microarc oxidation and electrophoresis technology, the problem of magnesium alloy being easily corrosive in the atmospheric environment is solved, and its corrosion resistance and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202510104322.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Magnesium alloys are prone to corrosion in atmospheric environments. The prior art such as microarc oxidation and electrophoresis technology have limitations in improving the corrosion resistance of magnesium alloys, especially products that cannot meet the needs of high corrosion resistance.
A magnesium alloy corrosion-resistant coating is used, and its formulation includes epoxy resin, phenolic resin, modified inorganic filler, butanol, toluene and monoethanolamine. A tough and dense coating is formed through microarc oxidation treatment and electrophoresis technology to enhance the corrosion resistance of magnesium alloy.
It significantly improves the corrosion resistance of magnesium alloy, enhances the adhesion and mechanical strength of the coating, and extends the corrosion resistance of magnesium alloy in neutral salt spray environment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloy processing and relates to a magnesium alloy corrosion-resistant coating and a use method thereof. Background Art
[0002] With the rapid development of the low-altitude economy, the weight of aircraft such as unmanned equipment and flying cars seriously affects their hovering time. Therefore, the research and development of lightweight materials has become an important task in the industry. Magnesium alloys stand out from many metals with their low density, excellent specific strength and specific stiffness. Although researchers have improved the composition and process, magnesium alloys still have high chemical activity and are prone to corrosion in the atmospheric environment, which greatly limits the use of magnesium alloys. It is currently believed that preparing an anti-corrosion coating on the surface of magnesium alloys to improve the corrosion resistance of materials has become a practical method. For products in general use environments, such as mobile phone frames, micro-arc oxidation technology is conventionally used to prepare a corrosion-resistant coating mainly composed of oxides on the surface of magnesium alloys by electrochemical methods. Its neutral salt spray resistance is in the range of 100-150 hours. However, for some products with higher corrosion resistance requirements, micro-arc oxidation cannot meet their needs. Electrophoresis technology is widely used in automotive primers because of its good corrosion resistance and easy processing. However, when electrophoresis is directly performed on magnesium alloys, the electrophoresis layer has poor bonding with the magnesium alloy, which makes the electrophoresis layer easy to peel off and fail to achieve the anti-corrosion effect. Therefore, there is a patent that combines the two to prepare a micro-arc oxidation technology that forms a coating in situ on the surface of the magnesium alloy. The coating has excellent bonding with the magnesium alloy, so researchers combined the two to prepare a micro-arc oxidation-electrophoresis composite coating, using the synergistic effect of the two to improve the corrosion resistance of the coating.
[0003] In the current patents, for the micro-arc oxidation-electrophoretic composite coating, the thickness of the micro-arc oxidation film in the Chinese patent publication number CN 118497863 A is about 25~30μm, and its corrosion resistance is about 3000h. It is the micro-arc oxidation-electrophoretic composite coating with the highest neutral salt spray resistance seen so far. Summary of the invention
[0004] The purpose of the present invention is to provide a magnesium alloy corrosion-resistant coating and a use method thereof, which has the characteristics of good corrosion resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A magnesium alloy corrosion-resistant coating, the coating formula is as follows, by mass percentage, 30-40% epoxy resin, 15-20% phenolic resin, 5-10% modified inorganic filler, 15-18% butanol, 10-15% toluene, 5-7% monoethanolamine, 2-3% dispersant, The preparation method of the modified inorganic filler is as follows: S1.1: titanium dioxide and zirconium nitrate were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h. The ground mixture was transferred to 600°C for roasting for 3 h. After the roasting was completed, it was cooled to room temperature, crushed and ground to obtain a mixture A; S1.2: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 30-40%, and mixture A is immersed in the sodium silicate solution, and ultrasonicated at 40°C for 1-2 hours, wherein the mass ratio of mixture A to sodium silicate is 1:(1-2). After the ultrasonication is completed, the mixture is filtered and dried to obtain mixture B; S1.3: dissolving graphene oxide in deionized water to obtain a graphene oxide solution with a mass fraction of 40-50%, immersing mixture B in the graphene oxide solution, and ultrasonicating for 1 h at room temperature, wherein the mass ratio of mixture B to graphene oxide is 1:1. After the ultrasonication is completed, filtering is performed to collect the filter cake; S1.4: The filter cake is placed in liquid nitrogen for freezing for 15 to 20 minutes, and then dried at -50°C for 6 hours under vacuum. After drying, the filter cake is crushed and ground to obtain the modified inorganic filler; The coating preparation method is as follows: Epoxy resin, phenolic resin, butanol, toluene and monoethanolamine are put into a reaction kettle, stirred at a speed of 200 r / min, and heated to 70°C while stirring. After complete dissolution, modified inorganic fillers and dispersants are added, the speed is increased to 250 r / min, and stirred for 4 to 6 hours to obtain the coating.
[0006] Furthermore, the dispersant is polyethylene glycol, and the number average molecular weight ranges from 2000 to 4000.
[0007] Furthermore, the particle size of the mixture A obtained by grinding in S1.1 is 500 mesh.
[0008] Furthermore, the particle size of the modified inorganic filler obtained by grinding in S1.4 is 800 mesh.
[0009] A method for using a magnesium alloy corrosion-resistant coating, the specific steps of the method are as follows: S5.1: Sodium phosphate, sodium fluoride and sodium hydroxide are mixed to form an electrolyte, the magnesium alloy after surface cleaning and drying is placed in an electrolytic cell, and micro-arc oxidation treatment is performed with the magnesium alloy as an anode and a stainless steel plate as a cathode to obtain a magnesium alloy substrate I after micro-arc oxidation treatment; S5.2: The emulsion KNT810-DN30 and the color paste KNT810-DH42 were mixed in a mass ratio of 5.7:1 to obtain a mixture C, the mixture C and the corrosion-resistant coating were mixed in a mass ratio of 1:1 to obtain a mixture D, and the mixture D was aged at 30° C. for 24 h and then attached to the surface of the magnesium alloy substrate I by electrophoresis treatment to obtain a magnesium alloy substrate II; S5.3: After the electrophoresis treatment is completed, the magnesium alloy substrate II is washed with pure water. After the washing is completed, it is baked and solidified.
[0010] Furthermore, the concentration of sodium phosphate in the electrolyte prepared in S5.1 is 10-15 g / L, the concentration of sodium fluoride is 4-8 g / L, the concentration of sodium hydroxide is 3-6 g / L, and the solvent is deionized water.
[0011] Furthermore, the pH of the electrolyte prepared in S5.1 is 12.9-13.1.
[0012] Furthermore, the parameters of the micro-arc oxidation treatment in S5.1 are constant current control, and the current density is 1.5~2.5A / dm 2 The frequency range is 1000~1500Hz, the duty cycle is 25~35%, the time is 5~12min. The thickness of the micro-arc oxidation coating is 8~15μm, and the electrolyte temperature is 25~35℃.
[0013] Furthermore, the parameters of the electrophoresis treatment in S5.2 are to adopt a constant voltage mode, the magnesium alloy substrate is the cathode, the stainless steel plate is the anode, the electrophoresis tank temperature is 30±0.5°C, the voltage is controlled to increase to 220V within 15s, and the duration is 5min.
[0014] Furthermore, the baking and curing parameters in S5.3 are a baking temperature of 175° C. and a baking time of 0.5 h.
[0015] The epoxy resin in the present invention was purchased from Shenyang Elex Chemical Co., Ltd. with a CAS number of 24969-06-0 and a purity of 99%; the phenolic resin in the present invention was purchased from Shenyang Elex Chemical Co., Ltd. with a CAS number of 9003-35-4 and a purity of 99%; the titanium dioxide in the present invention was purchased from Tianjin Linyi Chemical Technology Co., Ltd. with a purity of 99%; the sodium silicate in the present invention was purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd. with a purity of 99%.
[0016] The present invention provides a magnesium alloy corrosion-resistant coating and a method for using the same. The coating formula and preparation process, as well as the pretreatment and electrophoresis treatment process of the magnesium alloy substrate, significantly improve the corrosion resistance of the magnesium alloy. The epoxy resin and phenolic resin in the coating provide a tough coating foundation, while the modified inorganic filler effectively enhances the density and adhesion of the coating through its special preparation process, further improving the corrosion resistance of the coating. At the same time, the optimization of the electrolyte formula and micro-arc oxidation treatment parameters enables a uniform and dense micro-arc oxidation coating to be formed on the surface of the magnesium alloy substrate, further enhancing the protective effect of the coating. The electrophoresis treatment ensures that the coating can be evenly and tightly attached to the surface of the magnesium alloy substrate, avoiding problems such as coating shedding or cracking. After baking and curing, a strong bond is formed between the coating and the magnesium alloy substrate, further improving the overall corrosion resistance.
[0017] By adding epoxy resin and phenolic resin, modified inorganic fillers and other additives, the coating can form a tough and dense protective film on the surface of the magnesium alloy, effectively isolating the corrosive medium, thereby significantly improving the corrosion resistance of the magnesium alloy. The resin and modified inorganic filler in the coating can enhance the adhesion and mechanical strength of the coating, making the coating less likely to fall off or be damaged when subjected to external forces.
[0018] The components such as titanium dioxide, zirconium nitrate, sodium silicate and graphene oxide in the modified inorganic filler can work synergistically to enhance the corrosion resistance and mechanical properties of the coating. The modified inorganic filler has good dispersibility and stability, can be evenly dispersed in the coating, and improve the overall performance of the coating.
[0019] After titanium dioxide and zirconium nitrate are ground in a ball mill, a tight composite structure is formed through chemical bonds and physical adsorption. This structure is further solidified during the roasting process to form a compound with excellent corrosion resistance. The surface of the composite structure is rich in active sites. The composite structure of titanium dioxide and zirconium nitrate is immersed in a sodium silicate solution and subjected to ultrasonic treatment. The silicate ions react chemically with the active sites on the surface of the structure to form a chemical bond of silicon oxygen (Si-O), which can not only enhance the bonding force between the filler and the resin matrix, but also improve the corrosion resistance and dispersibility of the filler. Graphene oxide is then used for modification to further enhance the mechanical strength and corrosion resistance of the coating.
[0020] Epoxy resin and phenolic resin are the main film-forming substances of the coating. They can form a tough and dense protective film to isolate the corrosion of the magnesium alloy from the corrosive medium. At the same time, they also have good adhesion and mechanical properties, which can enhance the overall performance of the coating. By compounding components such as titanium dioxide, zirconium nitrate, sodium silicate and graphene oxide, a modified inorganic filler with excellent performance is formed. It can significantly improve the corrosion resistance and mechanical properties of the coating, while improving the dispersibility and stability of the coating. Butanol and toluene are used as solvents, which can dissolve resins and other additives to make the coating form a uniform liquid state, which is convenient for construction and coating. At the same time, they can also adjust the viscosity and fluidity of the coating to ensure that the coating can be evenly and smoothly attached to the surface of the magnesium alloy; monoethanolamine is used as an additive, which can adjust the pH value of the coating and improve the stability and dispersibility of the coating. At the same time, it can also react chemically with components such as resin to form a stronger chemical bond, enhancing the adhesion and mechanical properties of the coating.
[0021] Beneficial effects of the present invention: The present invention combines micro-arc oxidation treatment and electrophoresis technology to form a new magnesium alloy corrosion-resistant coating preparation technology. This technology not only improves the corrosion resistance of the coating, but also enhances the adhesion and aesthetics of the coating. Through the proportion of emulsion, color paste and coating, a coating formula with good corrosion resistance and aesthetics is formulated; the present invention adjusts the micro-arc oxidation to control the film thickness within the range of 8-15μm, combined with KNT810 cathode electrophoretic paint and corrosion-resistant coating, so that the treated magnesium alloy has better corrosion resistance; at the same time, because the film layer of the magnesium alloy is controlled within the range of 8-15μm during micro-arc oxidation, the production time required is significantly shortened, thereby reducing the energy consumption of the micro-arc oxidation process and increasing production efficiency. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] Example 1 A magnesium alloy corrosion-resistant coating, the coating formula is as follows, by mass percentage, epoxy resin 40%, phenolic resin 17%, modified inorganic filler 10%, butanol 15%, toluene 10%, monoethanolamine 5%, polyethylene glycol 2000 3%, The preparation method of the modified inorganic filler is as follows: S1.1: titanium dioxide and zirconium nitrate were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h. The ground mixture was transferred to 600°C for roasting for 3 h. After the roasting was completed, it was cooled to room temperature, crushed and ground to obtain a mixture A, and the particle size of the mixture A was 500 mesh; S1.2: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 35%, and mixture A is immersed in the sodium silicate solution, and ultrasonicated at 40°C for 2 hours, wherein the mass ratio of mixture A to sodium silicate is 1:1. After the ultrasonication is completed, the mixture is filtered and dried to obtain mixture B; S1.3: dissolving graphene oxide in deionized water to obtain a graphene oxide solution with a mass fraction of 45%, immersing mixture B in the graphene oxide solution, and ultrasonicating for 1 h at room temperature, wherein the mass ratio of mixture B to graphene oxide is 1:1. After the ultrasonication is completed, filtering is performed to collect the filter cake; S1.4: The filter cake is placed in liquid nitrogen for freezing for 15 minutes, and then dried at -50°C for 6 hours under vacuum. After drying, the filter cake is crushed and ground to obtain the modified inorganic filler, wherein the particle size of the modified inorganic filler is 800 mesh; The coating preparation method is as follows: Epoxy resin, phenolic resin, butanol, toluene and monoethanolamine are put into a reaction kettle, stirred at a speed of 200 r / min, and heated to 70°C while stirring. After complete dissolution, modified inorganic fillers and dispersants are added, the speed is increased to 250 r / min, and stirred for 6 hours to obtain the coating.
[0024] A method for using a magnesium alloy corrosion-resistant coating, the specific steps of the method are as follows: S5.1: Sodium phosphate, sodium fluoride and sodium hydroxide are mixed to form an electrolyte. The concentration of sodium phosphate in the electrolyte is 10g / L, the concentration of sodium fluoride is 8g / L, and the concentration of sodium hydroxide is 6g / L. The solvent is deionized water. The pH of the electrolyte is 12.9-13.1. The magnesium alloy after surface cleaning and drying is placed in an electrolytic cell. The magnesium alloy is used as the anode and the stainless steel plate is used as the cathode for micro-arc oxidation treatment. The parameters of the micro-arc oxidation treatment are constant current control mode and the current density is 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, and the time is 7min. The thickness of the micro-arc oxidation coating is 8μm, the electrolyte temperature is 30℃, and the magnesium alloy substrate I after micro-arc oxidation treatment is obtained; S5.2: The emulsion KNT810-DN30 and the color paste KNT810-DH42 were mixed at a mass ratio of 5.7:1 to obtain a mixture C, and the mixture C and the corrosion-resistant coating were mixed at a mass ratio of 1:1 to obtain a mixture D. The mixture D was aged at 30°C for 24 hours and then attached to the surface of the magnesium alloy substrate I by electrophoresis treatment. The parameters of the electrophoresis treatment were that the constant voltage mode was adopted, the magnesium alloy substrate was the cathode, the stainless steel plate was the anode, the temperature of the electrophoresis tank was 30±0.5°C, and the voltage was controlled to increase to 220V within 15s for 5 minutes, thereby obtaining a magnesium alloy substrate II; S5.3: After the electrophoresis treatment is completed, the magnesium alloy substrate II is washed with pure water. After the washing is completed, it is baked and cured. The baking and curing parameters are a baking temperature of 175°C and a baking time of 0.5h.
[0025] Example 2 A magnesium alloy corrosion-resistant coating, the coating formula is as follows, by mass percentage, 30% epoxy resin, 20% phenolic resin, 10% modified inorganic filler, 18% butanol, 15% toluene, 5% monoethanolamine, 2% polyethylene glycol 2000, The preparation method of the modified inorganic filler is as follows: S1.1: titanium dioxide and zirconium nitrate were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h. The ground mixture was transferred to 600°C for roasting for 3 h. After the roasting was completed, it was cooled to room temperature, crushed and ground to obtain a mixture A, and the particle size of the mixture A was 500 mesh; S1.2: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 30%, and mixture A is immersed in the sodium silicate solution, and ultrasonicated at 40°C for 1 hour, wherein the mass ratio of mixture A to sodium silicate is 1:1. After the ultrasonication is completed, the mixture is filtered and dried to obtain mixture B; S1.3: dissolving graphene oxide in deionized water to obtain a graphene oxide solution with a mass fraction of 40%, immersing mixture B in the graphene oxide solution, and ultrasonicating for 1 h at room temperature, wherein the mass ratio of mixture B to graphene oxide is 1:1. After the ultrasonication is completed, filtering is performed to collect the filter cake; S1.4: The filter cake is placed in liquid nitrogen for freezing for 15 minutes, and then dried at -50°C for 6 hours under vacuum. After drying, the filter cake is crushed and ground to obtain the modified inorganic filler, wherein the particle size of the modified inorganic filler is 800 mesh; The coating preparation method is as follows: Epoxy resin, phenolic resin, butanol, toluene and monoethanolamine are put into a reaction kettle, stirred at a speed of 200 r / min, and heated to 70°C while stirring. After complete dissolution, modified inorganic fillers and dispersants are added, the speed is increased to 250 r / min, and stirred for 4 hours to obtain the coating.
[0026] A method for using a magnesium alloy corrosion-resistant coating, the specific steps of the method are as follows: S5.1: Sodium phosphate, sodium fluoride and sodium hydroxide are mixed to form an electrolyte. The concentration of sodium phosphate in the electrolyte is 10g / L, the concentration of sodium fluoride is 4g / L, and the concentration of sodium hydroxide is 3g / L. The solvent is deionized water. The pH of the electrolyte is 12.9-13.1. The magnesium alloy after surface cleaning and drying is placed in an electrolytic cell. The magnesium alloy is used as the anode and the stainless steel plate is used as the cathode for micro-arc oxidation treatment. The parameters of the micro-arc oxidation treatment are constant current control mode and the current density is 1.5A / dm 2 , the frequency range is 1000Hz, the duty cycle is 25%, and the time is 12min. The thickness of the micro-arc oxidation coating is 8μm, the electrolyte temperature is 25℃, and the magnesium alloy substrate I after micro-arc oxidation treatment is obtained; S5.2: The emulsion KNT810-DN30 and the color paste KNT810-DH42 were mixed at a mass ratio of 5.7:1 to obtain a mixture C, and the mixture C and the corrosion-resistant coating were mixed at a mass ratio of 1:1 to obtain a mixture D. The mixture D was aged at 30°C for 24 hours and then attached to the surface of the magnesium alloy substrate I by electrophoresis treatment. The parameters of the electrophoresis treatment were that the constant voltage mode was adopted, the magnesium alloy substrate was the cathode, the stainless steel plate was the anode, the temperature of the electrophoresis tank was 30±0.5°C, and the voltage was controlled to increase to 220V within 15s for 5 minutes, thereby obtaining a magnesium alloy substrate II; S5.3: After the electrophoresis treatment is completed, the magnesium alloy substrate II is washed with pure water. After the washing is completed, it is baked and cured. The baking and curing parameters are a baking temperature of 175°C and a baking time of 0.5h.
[0027] Example 3 A magnesium alloy corrosion-resistant coating, the coating formula is as follows, by mass percentage, epoxy resin 40%, phenolic resin 15%, modified inorganic filler 5%, butanol 15%, toluene 15%, monoethanolamine 7%, polyethylene glycol 2000 3%, The preparation method of the modified inorganic filler is as follows: S1.1: titanium dioxide and zirconium nitrate were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h. The ground mixture was transferred to 600°C for roasting for 3 h. After the roasting was completed, it was cooled to room temperature, crushed and ground to obtain a mixture A, and the particle size of the mixture A was 500 mesh; S1.2: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 40%, and mixture A is immersed in the sodium silicate solution, and ultrasonicated at 40°C for 2 hours, wherein the mass ratio of mixture A to sodium silicate is 1:2. After the ultrasonication is completed, the mixture is filtered and dried to obtain mixture B; S1.3: dissolving graphene oxide in deionized water to obtain a graphene oxide solution with a mass fraction of 50%, immersing mixture B in the graphene oxide solution, and ultrasonicating for 1 h at room temperature, wherein the mass ratio of mixture B to graphene oxide is 1:1. After the ultrasonication is completed, filtering is performed to collect the filter cake; S1.4: The filter cake is placed in liquid nitrogen for freezing for 20 minutes, and then dried at -50°C for 6 hours under vacuum. After drying, the filter cake is crushed and ground to obtain the modified inorganic filler, wherein the particle size of the modified inorganic filler is 800 mesh; The coating preparation method is as follows: Epoxy resin, phenolic resin, butanol, toluene and monoethanolamine are put into a reaction kettle, stirred at a speed of 200 r / min, and heated to 70°C while stirring. After complete dissolution, modified inorganic fillers and dispersants are added, the speed is increased to 250 r / min, and stirred for 6 hours to obtain the coating.
[0028] A method for using a magnesium alloy corrosion-resistant coating, the specific steps of the method are as follows: S5.1: Sodium phosphate, sodium fluoride and sodium hydroxide are mixed to form an electrolyte. The concentration of sodium phosphate in the electrolyte is 15g / L, the concentration of sodium fluoride is 8g / L, and the concentration of sodium hydroxide is 6g / L. The solvent is deionized water. The pH of the electrolyte is 12.9-13.1. The magnesium alloy after surface cleaning and drying is placed in an electrolytic cell. The magnesium alloy is used as the anode and the stainless steel plate is used as the cathode for micro-arc oxidation treatment. The parameters of the micro-arc oxidation treatment are constant current control mode and the current density is 2.5A / dm 2 , the frequency range is 1500Hz, the duty cycle is 35%, and the time is 5min. The thickness of the micro-arc oxidation coating is 15μm, the electrolyte temperature is 35℃, and the magnesium alloy substrate I after micro-arc oxidation treatment is obtained; S5.2: The emulsion KNT810-DN30 and the color paste KNT810-DH42 were mixed at a mass ratio of 5.7:1 to obtain a mixture C, and the mixture C and the corrosion-resistant coating were mixed at a mass ratio of 1:1 to obtain a mixture D. The mixture D was aged at 30°C for 24 hours and then attached to the surface of the magnesium alloy substrate I by electrophoresis treatment. The parameters of the electrophoresis treatment were that the constant voltage mode was adopted, the magnesium alloy substrate was the cathode, the stainless steel plate was the anode, the temperature of the electrophoresis tank was 30±0.5°C, and the voltage was controlled to increase to 220V within 15s for 5 minutes, thereby obtaining a magnesium alloy substrate II; S5.3: After the electrophoresis treatment is completed, the magnesium alloy substrate II is washed with pure water. After the washing is completed, it is baked and cured. The baking and curing parameters are a baking temperature of 175°C and a baking time of 0.5h.
[0029] Comparative Example 1 In this comparative example, zirconium nitrate was not added during the modification process of the inorganic filler, and the remaining steps were consistent with those of Example 1.
[0030] Comparative Example 2 In this comparative example, no sodium silicate was added during the modification of the inorganic filler, and the remaining steps were consistent with those of Example 1.
[0031] Comparative Example 3 In this comparative example, graphene oxide is not added during the modification process of the inorganic filler, and the remaining steps are consistent with those of Example 1.
[0032] The corrosion resistance of the embodiment and the comparative example was tested according to ISO 9227:2017. The sample was fixed, and the concentration of 10% sodium chloride was adjusted with 3% hydrochloric acid to a pH value of 3 to prepare brine, which was sprayed on the sample through a spray device. The spray volume was 20 mL / s, the spray frequency was 60 min / time, each spray was 20 s, and after continuous spraying for 168 h, the corrosion of the sample was observed. The experimental results are summarized in the following table:
[0033] It can be seen from the above experiments that the coating prepared by the present invention can make the magnesium alloy have better corrosion resistance.
[0034] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A magnesium alloy corrosion-resistant coating, characterized in that: The coating formula is as follows: by mass percentage, epoxy resin 30-40%, phenolic resin 15-20%, modified inorganic filler 5-10%, butanol 15-18%, toluene 10-15%, monoethanolamine 5-7%, dispersant 2-3%, The preparation method of the modified inorganic filler is as follows: S1.1: titanium dioxide and zirconium nitrate were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h. The ground mixture was transferred to 600°C for roasting for 3 h. After the roasting was completed, it was cooled to room temperature, crushed and ground to obtain a mixture A; S1.2: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 30-40%, and mixture A is immersed in the sodium silicate solution, and ultrasonicated at 40°C for 1-2 hours, wherein the mass ratio of mixture A to sodium silicate is 1:(1-2). After the ultrasonication is completed, the mixture is filtered and dried to obtain mixture B; S1.3: dissolving graphene oxide in deionized water to obtain a graphene oxide solution with a mass fraction of 40-50%, immersing mixture B in the graphene oxide solution, and ultrasonicating for 1 h at room temperature, wherein the mass ratio of mixture B to graphene oxide is 1:
1. After the ultrasonication is completed, filtering is performed to collect the filter cake; S1.4: The filter cake is placed in liquid nitrogen for freezing for 15 to 20 minutes, and then dried at -50°C for 6 hours under vacuum. After drying, the filter cake is crushed and ground to obtain the modified inorganic filler; The coating preparation method is as follows: Epoxy resin, phenolic resin, butanol, toluene and monoethanolamine are put into a reaction kettle, stirred at a speed of 200 r / min, and heated to 70°C while stirring. After complete dissolution, modified inorganic fillers and dispersants are added, the speed is increased to 250 r / min, and stirred for 4 to 6 hours to obtain the coating.
2. The magnesium alloy corrosion-resistant coating according to claim 1, characterized in that: The dispersant is polyethylene glycol, and the number average molecular weight ranges from 2000 to 4000.
3. The magnesium alloy corrosion-resistant coating according to claim 1, characterized in that: The particle size of the mixture A obtained by grinding in S1.1 is 500 mesh.
4. The magnesium alloy corrosion-resistant coating according to claim 1, characterized in that: The particle size of the modified inorganic filler obtained by grinding in S1.4 is 800 mesh.
5. A method for using a magnesium alloy corrosion-resistant coating, based on the magnesium alloy corrosion-resistant coating according to any one of claims 1 to 4, characterized in that: The specific steps of the method of use are as follows: S5.1: Sodium phosphate, sodium fluoride and sodium hydroxide are mixed to form an electrolyte, the magnesium alloy after surface cleaning and drying is placed in an electrolytic cell, and micro-arc oxidation treatment is performed with the magnesium alloy as an anode and a stainless steel plate as a cathode to obtain a magnesium alloy substrate I after micro-arc oxidation treatment; S5.2: The emulsion KNT810-DN30 and the color paste KNT810-DH42 were mixed in a mass ratio of 5.7:1 to obtain a mixture C, the mixture C and the corrosion-resistant coating were mixed in a mass ratio of 1:1 to obtain a mixture D, and the mixture D was aged at 30° C. for 24 h and then attached to the surface of the magnesium alloy substrate I by electrophoresis treatment to obtain a magnesium alloy substrate II; S5.3: After the electrophoresis treatment is completed, the magnesium alloy substrate II is washed with pure water. After the washing is completed, it is baked and solidified.
6. The method for using the magnesium alloy corrosion-resistant coating according to claim 5, characterized in that: The electrolyte prepared in S5.1 has a sodium phosphate concentration of 10-15 g / L, a sodium fluoride concentration of 4-8 g / L, a sodium hydroxide concentration of 3-6 g / L, and the solvent is deionized water.
7. The method for using the magnesium alloy corrosion-resistant coating according to claim 5, characterized in that: The pH of the electrolyte prepared in S5.1 is 12.9-13.
1.
8. The method for using the magnesium alloy corrosion-resistant coating according to claim 5, characterized in that: The parameters of the micro-arc oxidation treatment in S5.1 are constant current control, and the current density is 1.5~2.5A / dm 2 , the frequency range is 1000~1500Hz, the duty cycle is 25~35%, the time is 5~12min, the film thickness of the micro-arc oxidation coating is 8~15μm, and the electrolyte temperature is 25~35℃.
9. The method for using the magnesium alloy corrosion-resistant coating according to claim 5, characterized in that: The parameters of the electrophoresis treatment in S5.2 are as follows: the constant voltage mode is adopted, the magnesium alloy substrate is the cathode, the stainless steel plate is the anode, the temperature of the electrophoresis tank is 30±0.5°C, the voltage is controlled to increase to 220V within 15s, and the duration is 5min.
10. The method for using the magnesium alloy corrosion-resistant coating according to claim 5, characterized in that: The baking curing parameters in S5.3 are a baking temperature of 175° C. and a baking time of 0.5 h.
Citation Information
Patent Citations
Method for improving bonding force between micro-arc oxidation and electrophoretic coating layers of rare earth magnesium alloy
CN118497863A
Corrosion-resistant magnesium alloy with multi-stage protective coating and preparation method of corrosion-resistant magnesium alloy
CN114713481A
Process for sealing micro pores of micro-arc oxide films
US20090324840A1
Corrosion-resistant magnesium alloy with a multi-level protective coating and preparation process thereof
US20230398571A1